PELAKSANAAN PUTUSAN (EKSEKUSI) PERKARA PERSELISIHAN HUBUNGAN INDUSTRIAL TERHADAP BADAN USAHA COMMANDITAIRE VENNOOTSCHAP (STUDI PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR 828K/Pdt.Sus-PHI/2016) - Hariyanto, Arif Wishnu Wardhana (Program Studi Magister Ilmu Hukum Universitas Kader Bangsa, 2019)
Industrial Relations Court is a special court that has the authority to examine and decide on industrial relations disputes, the execution of decisions of the Industrial Relations Court is not an easy matter because many factors that inhibit include the absence of goods or assets that can be submitted for execution, especially if the Respondent is an entity in the form of a Vennotschap (CV) Commanditaire. The formulation of the problem in this study is 1) How is the execution of the case of an industrial relations dispute on the business entity Commanditaire Vennotschap (CV) as the execution of the decision of the Supreme Court of the Republic of Indonesia Number 828K / Pdt.Sus-PHI / 2016 ?; and 2) What are the obstacles that occur in the execution of cases of industrial relations disputes against the business entity of the Commanditaire Vennotschap (CV) ?. The research method used is normative juridical legal research. The data sources used in this study consist of primary data and secondary data. Based on the results of the study show that: 1) The implementation of the decision on the case of an industrial relations dispute against the business entity Commanditaire Vennotschap (CV) as the execution of the decision of the Supreme Court of the Republic of Indonesia Number 828K / Pdt.Sus-PHI / 2016 cannot be carried out until this applicant does not find goods / assets belonging to the Defendant or the respondent of the execution, namely the Trisakti CV; and 2) Constraints that occur in the implementation of decisions on cases of industrial relations disputes against the business entity of the Vennotschap Commanditaire (CV), namely a) Juridical barriers covering 1) There is resistance from third parties (Derden Verzet); 2) There is resistance from the defendant's execution party; 3) There is a request for a review; and b) Non-juridical obstacles include 1) Absence of goods or assets that can be submitted for execution; 2) There is physical resistance from the defendant's execution; 3) The presence of third party hands; 4) Less than optimal role of the Court; and 5) No withdrawal of complementary allies or allies of management as Defendant. Keywords: Verdict, execution, industrial relations dispute.